The end of a two-state settlement? Alternatives and priorities for settling the Israeli-Palestinian conflict - Muriel Asseburg; Jan Busse (Stiftung Wissenschaft und Politik (SWP), 2016)
On the occasion of their joint government consultations in February 2016, Prime Minister Benjamin Netanyahu and Chancellor Angela Merkel stressed that this was not the time for making major progress in the Israeli-Palestinian peace process, given the instability in the Middle East. However, merely adhering to a two-state settlement as a mantra without taking any concrete steps to implement it effectively reinforces the one-state reality under Israeli dominance. Ultimately, this will make settling the conflict impossible. Popular support for a two-state solution is waning on both sides. While at present alternative one-state or confederate models have even slimmer chances of being realized, Germany and the EU should nevertheless explore the creative and constructive aspects of these models, which would enable the two sides to maintain their national identities as well as realize their individual and collective rights. Their priority, however, should be to alter the cost-benefit calculation of the parties to the conflict, so as to generate the political will for bringing about a settlement at all. (SWP Comments)
Keywords: 320